2012
DOI: 10.1038/nature11581
|View full text |Cite
|
Sign up to set email alerts
|

Novel Foxo1-dependent transcriptional programs control Treg cell function

Abstract: Regulatory T (Treg) cells, characterized by expression of the transcription factor forkhead box P3 (Foxp3), maintain immune homeostasis by suppressing self-destructive immune responses1–4. Foxp3 operates as a late-acting differentiation factor controlling Treg cell homeostasis and function5, whereas the early Treg-cell-lineage commitment is regulated by the Akt kinase and the forkhead box O (Foxo) family of transcription factors6–10. However, whether Foxo proteins act beyond the Treg-cell-commitment stage to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
429
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 373 publications
(451 citation statements)
references
References 44 publications
14
429
0
1
Order By: Relevance
“…Removal of this regulation in T Reg cells with PTEN deficiency results in severely compromised T Reg cell stability and in their conversion into inflammatory T H 1 and T H 17 cells 79,80 . Dampened AKT activity in T Reg cells supports the expression of IL-2 receptor α-chain (IL-2Rα; also known as CD25) and the nuclear localization of forkhead box O (FOXO) transcription factors, both of which are crucial for preventing T Reg cell plasticity towards inflammatory programmes [79][80][81] . Additionally, neuropilin 1, a receptor that is highly expressed by mouse tT Reg cells, recruits PTEN to the immunological synapse and blocks the activation of AKT during TCR stimulation, thus promoting T Reg cell stability and function 82 .…”
Section: Box 2 | Phenotypic Plasticity In Inflammatory and Regulatorymentioning
confidence: 99%
“…Removal of this regulation in T Reg cells with PTEN deficiency results in severely compromised T Reg cell stability and in their conversion into inflammatory T H 1 and T H 17 cells 79,80 . Dampened AKT activity in T Reg cells supports the expression of IL-2 receptor α-chain (IL-2Rα; also known as CD25) and the nuclear localization of forkhead box O (FOXO) transcription factors, both of which are crucial for preventing T Reg cell plasticity towards inflammatory programmes [79][80][81] . Additionally, neuropilin 1, a receptor that is highly expressed by mouse tT Reg cells, recruits PTEN to the immunological synapse and blocks the activation of AKT during TCR stimulation, thus promoting T Reg cell stability and function 82 .…”
Section: Box 2 | Phenotypic Plasticity In Inflammatory and Regulatorymentioning
confidence: 99%
“…While most research efforts to date on miR-27 have been primarily focused on its role in tumorigenesis and embryonic stem cell differentiation (23)(24)(25)(26), many miR-27 targets identified in those studies such as FOXO1, runt-related transcription factor 1 (RUNX1), and SMAD2/3 were known to regulate Treg biology as well (27)(28)(29)(30)(31)(32). We found that, while FOXO1 did not seem to be repressed by miR-27 in T cells, markedly diminished SMAD2/3 and RUNX1 protein levels were detected in T cells that overexpressed miR-27 (Supplemental Figure 6).…”
Section: Mir-27 Targets C-rel a Member Of The Nf-κb Transcription Famentioning
confidence: 99%
“…Taken together, these data indicate that AnxA1 does not directly induce differentiation of niT cells, but it may facilitate the transfer of neutrophil-derived signaling proteins necessary for niT-cell formation. The transcription factor FOXO1 is the master regulator necessary for FOXP3 expression in inducible Tregs (34)(35)(36). Intriguingly, FOXO1 is expressed by neutrophils, where it is endowed with proapoptotic functions (37).…”
Section: Depletion Of Neutrophils During Pregnancy Leads To Impairedmentioning
confidence: 99%